THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIPS AND ORGANIZATIONAL COMMITMENT TO TURNOVER INTENTION THROUGH JOB SATISFACTION AS A MEDIATOR - Lystia Tri Utami; M. Havidz Aima (Dinasti International Journal of Education Management And Social Science, 2021)
This research aims to uncovered and evaluated those issues which related to the influences that appeared from transformational leadership and organizational commitment towards turnover intention through job satisfaction as a mediator at Operational Directorate employees of PT XYZ. The design which currently used in this research was causality analysis to revealed the connection between each variables. The population in this research was all the employees from Operational Directorate of PT. XYZ which amounted to 1084 employees. The sampling method was performed by simple random sampling with a total of 233 respondents. The data analysis method used SEM-PLS with the results showed that transformational leadership and organizational commitment had a positive and significant impact on job satisfaction. Transformational leadership has no affect towards turnover intention, but the organizational commitment and job satisfaction had a positive and significant impact on turnover intention. The transformational leadership and organizational commitment had a simultaneous impact towards job satisfaction. And the Transformational leadership, organizational commitment and job satisfaction had simultaneous impact towards turnover intention. Job satisfaction has fully mediates the affect which appears from transformational leadership and organizational commitment towards turnover intention.